Penerapan Manajemen Peserta Didik Berbasis Pesantren di Pondok Pesantren Al Ma'arif Bilae Kab. Bone - jentak, Sulaeman ali (Atta'dib Jurnal Pendidikan Agama Islam, 2023)
This research was conducted in order to find out the Implementation of Learner Management in a boarding school (pondok pesantren). This article aims to find out about the Implementation of Pesantren-Based Learner Management at Al Ma'arif Bilae Boarding School in Bone Regency. The type of research used is qualitative research with data collection techniques using observation, interview, and documentation. The results showed that the implementation of learner management at Pondok Pesantren Al Ma'arif Bilae Boarding School in Bone Regency has been carried out quite well. The interesting thing about the implementation of pesantren-based learner management is that in the admission of students, the learner data base has been inputted in an EMIS (Education Management Information System) application, including if there are participants who want to mutate/move from or to another madrasah, this EMIS application can be used to mutate/move through communication between madrasah operators. On the other hand, certain parts still need improvement, especially in the planning of students where the boarding school needs to make careful preparations, especially in preparing better socialization by socializing superior programs such as the Quran tahfiz program, other things regarding the code of ethics, discipline of students Some who do not implement the rules or norms that apply in the boarding school even come not on time. On the other hand, some teachers sometimes come late, and some do not even come at all when it is time to teach, so the class is empty. This certainly shows a poor performance, so it is necessary to improve and collaborate with all parties so that the management of students in the future will be much better.Â Keywords: Learner Management, Boarding School.